HOW LEADERSHIP AND INTEGRITY AFFECT EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT - Sabil, Sabil; Hakim, Lukman; Martias, Andi; Kamal, Fahmi; Oktiani, Nurvi; Sudarmono Hadi, Seno; Masahere, Usran; Wiyanti, Rahma (AGUSPATI Research Institute, 2021)
The company's growth is expected to be faster in order to survive in the competition, in the current digital era the number of competitors cannot be known for sure because many are moving digitally. so that in this study the researchers saw the importance of organizational commitment and the role of employees in advancing the company in the current digital era, therefore this study aims to determine the factors that influence this and how much influence leadership and integrity have on it. This study uses the analytical method used is descriptive analysis, and the test instrument using SEM PLS with the number of samples used as many as 140 permanent employees in one of the company's departments. The results of the study indicate that leadership and integrity partially and significantly affect organizational commitment and employee performance. While simultaneously leadership and integrity have a significant effect on employee performance by mediating Organizational Commitment.